Test anxiety and its consequences on academic performance among university students - Bin Kassim M.A.; Bt Mohd Hanafi S.R.; Hancock D.R. (Nova Science Publishers, Inc., 2023)
Some educators have failed to acknowledge the prevalence of test anxiety and its effect on academic performance among university students. This study addresses this issue at the university level using data collected through the Revised Test Anxiety (RTA) instrument and Sarason's four-factor model as a basis for measuring test anxiety. The study also investigates the effect of demographic factors on test anxiety. Findings reveal that test anxiety is significantly and negatively related to academic performance. Reasons for these findings are addressed. 2009 by Nova Science Publishers, Inc. All Rights Reserved.